Analysis of Occupational Safety Policies in the Manufacturing Industry Related to Compliance and its Impact on Occupational Accidents - Christy Gery Buyang; Made Dewi Sariyani; Jim Briand Kolianan (Miracle Journal Get Press, 2024)
Occupational safety is a very important aspect in the manufacturing industry, given the high risk of work accidents that can occur in this environment. The manufacturing industry is known for the use of heavy machinery, hazardous chemicals, and complex production processes, which increase the chance of occupational accidents if there is no effective work safety system (Fauzi, 2024). This research uses quantitative and qualitative approaches (mixed methods). The quantitative approach was used to measure the level of compliance with work safety policies and its impact on work accidents. Table 1 shows that the variables of knowledge, motivation and personality have a significant value > 0.05. Table 2 shows that the variables of training and communication do not have a significant relationship with labour compliance in using PPE. Table 3 shows that the PPE availability variable does not have a significant relationship with labour compliance in using PPE. It is important that companies continue to develop and implement comprehensive safety policies, involve workers in the drafting process, and provide ongoing training to create a safer and more productive work environment.